The Impact of Direct and Indirect Experience of Insurance Services on Customer-Based Brand Equity Some Research Questions and Implications - Hassan, Ghorbani; Seyedeh Masoomeh, Abdollahi; Mohammad Reza, Dalvi Esfahan (Richtmann Publishing, 2013)
Brand equity has been introduced as a key issue in marketing. A crucial communication task for unknown brands is to build thebrand knowledge in consumers’ minds necessary to become established. This study explores the way in which brand equityand quality of experience are developed in insurance industry from customer's perspective, providing a conceptual framework.The statistical population consists of customers who have used services offered by Parsian Insurance Company's branches inIsfahan city. Random sampling method has been applied to select the appropriate sample. The examinations were donethrough 185 available questionnaires. In order to test the conceptual model, structural equations' model (SEM) has been used.Results based on SEM outputs demonstrate acceptance and confirmation of all studied factors. These findings indicate thatadvertising spend, word of mouth and service performance have a positive impact on quality of experience, while monetarypromotion influence the dependent variable negatively. Quality of experience also has a positive relation with overall brandequity.